2006
DOI: 10.1126/science.1123570
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic Abundance of the N 2 -Fixing Colonial Cyanobacterium Trichodesmium

Abstract: Colonial diazotrophic cyanobacteria of the genus Trichodesmium are thought to play a significant role in the input of new nitrogen to upper layers of the tropical and subtropical oceanic ecosystems that cover nearly half of Earth's surface. Here we describe results of a transatlantic survey in which a noninvasive underwater digital microscope (the video plankton recorder), was towed across the North Atlantic at 6 meters per second while undulating between the surface and 130 meters. Colony abundance had a basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 23 publications
16
177
4
Order By: Relevance
“…It has been hypothesized that this organism may migrate to the phosphocline, store P as polyP, and return to the surface in a process termed P-mining (Karl et al 1992;Villareal and Carpenter 2003). Although this could result in elevated polyP, the phosphocline ranged from 160 to 300 m on this transect, which is deeper than Trichodesmium is likely to migrate (White et al 2006a), and is deeper than Trichodesmium is typically observed in this region (Orcutt et al 2001;Davis and McGillicuddy 2006). Additionally, a study from the Caribbean found that polyP granules in Trichodesmium were more abundant in negatively buoyant colonies than in positively buoyant colonies, the opposite trend from what you would expect if P-mining were occurring (Romans et al 1994).…”
Section: Discussionmentioning
confidence: 98%
“…It has been hypothesized that this organism may migrate to the phosphocline, store P as polyP, and return to the surface in a process termed P-mining (Karl et al 1992;Villareal and Carpenter 2003). Although this could result in elevated polyP, the phosphocline ranged from 160 to 300 m on this transect, which is deeper than Trichodesmium is likely to migrate (White et al 2006a), and is deeper than Trichodesmium is typically observed in this region (Orcutt et al 2001;Davis and McGillicuddy 2006). Additionally, a study from the Caribbean found that polyP granules in Trichodesmium were more abundant in negatively buoyant colonies than in positively buoyant colonies, the opposite trend from what you would expect if P-mining were occurring (Romans et al 1994).…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, variability in the chemical and physical environment in the oceans can be more predictable with depth than across space. For exemple, the abundance of different species can vary predictably with depth (Belyayeva, 1970;Letelier et al, 1993;Bidigare and Ondrusek, 1996;Johnson et al, 2006;DeLong et al, 2006) as well as latitude (Davis and McGillicuddy, 2005) and longitude (Cavender-Bares et al, 2001). In all cases, abundance of particular taxonomic groups is closely tied to the chemical and physical environment.…”
Section: The Physical Generation Of Variabilitymentioning
confidence: 99%
“…It seems unlikely that the activity of large buoyant genera such as Trichodesmium can wholly explain the subsurface CH 4 features given that Trichodesmium are largely observed within or at the base of surface mixed layer 25,26 and that CH 4 supersaturation has also been observed outside of the subtropical gyres 27 . Alternately, observations of CH 4 maxima below the surface mixed layer and the lack of diurnal variation of these CH 4 levels 6 point to heterotrophic organisms as probable contributors to CH 4 production-provided a steady source of MPn is available and that environmental conditions favour the utilization of dissolved organic phosphorus (DOP).…”
mentioning
confidence: 99%